Tooth Discoloration Resulting from a Nano Zinc Oxide-Eugenol Sealer - Zarei, Mina; Javidi, Maryam; Jafari, Marzieh; Gharechahi, Maryam; Javidi, Pedram; Shayani Rad, Maryam (Iranian Endodontic Journal, 2016)
Introduction: A desirable quality of any endodontic sealer is its ability to be tooth color friendly. Therefore the aim of the present study was to evaluate the tooth discoloration potential of a nano zinc oxide-eugenol (NZOE) sealer. Methods and Materials: In order to evaluate tooth discoloration, the pulp chamber of 60 human maxillary central and lateral incisors were filled with one of the sealers, naming AH-26 (resin-based sealer), Pulpdent sealer (ZOE-based) and a NZOE experimental sealer. Color measurements was assessed at the baseline (before placement of sealers) (T0), 24 h (T1) and 72 h (T2) h, 1-week (T3), and 1-month (T4) after the placement of sealers using the Easy Shade spectrophotometer. Data were analyzed in SPSS software using one-way ANOVA, and repeated measured ANOVA. Results: No significant differences were observed when the paired comparison test was performed (P>0.05). Conclusion: The tested nZOE sealer had similar tooth discoloration potential in comparison with AH-26 and ZOE sealer. Keywords: Nano Particle; Root Canal Sealer; Tooth Discoloration; Spectrophotometry; Zinc-Oxide Eugenol